2015
DOI: 10.1007/s00572-014-0623-2
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of genes involved in N-acetylglucosamine uptake and metabolism suggests a recycling mode of chitin in intraradical mycelium of arbuscular mycorrhizal fungi

Abstract: Arbuscular mycorrhizal (AM) fungi colonize roots and form two kinds of mycelium, intraradical mycelium (IRM) and extraradical mycelium (ERM). Arbuscules are characteristic IRM structures that highly branch within host cells in order to mediate resource exchange between the symbionts. They are ephemeral structures and at the end of their life span, arbuscular branches collapse from the tip, fungal cytoplasm withdraws, and the whole arbuscule shrinks into fungal clumps. The exoskeleton of an arbuscule contains s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…of chitin in intraradical mycelium of arbuscular mycorrhizal fungi (Kobae et al 2015). GlcNAc signaling is also important for a broad range of organisms beyond the fungal kingdom, as it regulates virulence functions in bacteria and inflammasome activation in mammalian cells Wolf et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…of chitin in intraradical mycelium of arbuscular mycorrhizal fungi (Kobae et al 2015). GlcNAc signaling is also important for a broad range of organisms beyond the fungal kingdom, as it regulates virulence functions in bacteria and inflammasome activation in mammalian cells Wolf et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that 74% of the bacteria associated with the spore walls of AMF had chitinolytic activity. Chitinolytic activity of bacteria also enhances AMF and plant root recognition [ 48 ] by stimulating the spores to produce more signaling molecules. In a recent study, Genre et al [ 49 ] reported that short-chain chitin oligomers produced by Gigaspora margarita triggered AM-related signaling pathway by inducing the nuclear Ca 2+ spiking in Medicago truncatula roots.…”
Section: Discussionmentioning
confidence: 99%
“…Specialized or more generic transmembrane transporters facilitate uptake of N-acetylglucosamine (a chitin monomer) to eukaryotic cells [3,107]. Interestingly, genes responsible for N-acetylglucosamine transport across membrane and its further metabolism have also been described from AM fungus Rhizophagus irregularis [75], yet they have only been documented to be active in the intraradical mycelium, possibly recycling organic N from collapsing arbuscules. Regardless of the possible role of N-acetylglucosamine (or other soluble products of chitinolysis) in N nutrition of various microorganisms, chitin oligomers and their derivatives (such as lipo-chitooligosaccharides) also serve as signals to recognize pathogens or symbionts in the plant and microbial worlds [5,93,108].…”
Section: Chitin-a Relevant Organic N Source For the Amf?mentioning
confidence: 99%